2014
DOI: 10.1111/head.12465
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Headaches in an Urban Slum in Enugu South East Nigeria: A Door‐to‐Door Survey

Abstract: Headache is a common health problem in an urban slum in Enugu south east Nigeria where 66.7% of participants had experienced headache in their lifetime, and 49.4% had experienced primary headaches. The prevalence of migraine and TTH were 6.4% (5% in males and 7.5% in females) and 13.8% (12.2% in males and 15.1% in females), respectively. The peak ages of migraine and tension-type headache were 30-39 and 60-69 years, respectively. The prevalence of primary headaches was significantly higher among subjects who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(89 reference statements)
2
6
0
Order By: Relevance
“…Headache is a common neurologic disorder worldwide [1]- [14]. The lifetime prevalence of primary headaches among medical and nursing students in this study was higher than the regional and continental average [15] and previous studies from Nigeria [1] [3] [6]- [13]. Similar to a previous study from the region there was no significant difference between males and females [13].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Headache is a common neurologic disorder worldwide [1]- [14]. The lifetime prevalence of primary headaches among medical and nursing students in this study was higher than the regional and continental average [15] and previous studies from Nigeria [1] [3] [6]- [13]. Similar to a previous study from the region there was no significant difference between males and females [13].…”
Section: Discussionsupporting
confidence: 73%
“…The male: female of 1:1.4 is similar to the continental average as well as local reports[13] [14][17]. Migraine without aura had the higher proportion than migraine with aura in the study.Similar results have been ob-O.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…6 However, a lower prevalence of migraine (<1%) was obtained in this survey, compared with global estimates of 3%-7% and local estimates of 5.3%-18.9%. [17][18][19][20][21][22] The older age of this study population may be a factor, as previously reported by Osuntokun et al, 7 where the highest age-specific prevalence was in the first decade of life. epilepsy A lower crude prevalence rate of 2.93 per 1000 was found, compared with global estimates (4-8 per 1000) and local studies (4.1-28 per 1000).…”
Section: Open Accessmentioning
confidence: 66%
“…lower than the 20% reported by others. 25,26 This may be due to between-study differences in population demographics and the possibility of selection bias in our study. Secondly, our study had a relatively small sample size, and further larger scale studies are required.…”
Section: Discussionmentioning
confidence: 93%